High Impact Educational Practice through First Year Experience: Case of Undergraduates in UNIMAS - Shafinah Begum, Abdul Rahim; Idawati, Ismail; Rohana, Sapawi (Science Research Societ, 2021)
A compulsory course known as Soft skills and Basic Volunteerism offered at Universiti Malaysia Sarawak (UNIMAS) adopted the High Impact EducationalPractices (HEIPs)through First YearExperience. This course aims at imparting soft skills among allstudents in UNIMAS, taken in their first semester of their program. The main course learning outcomes are to develop personal and social skills, academic skills, and conduct volunteerism activities. The course learning units were designed to assiststudents adapting smoothly to the new university environment while improving academic and people skills. A survey to gauge students’ perception about their learning skills was conducted before the course began and another survey was conducted after the course ended. In the assessment, the studentsreported group activitiesrelating to meeting faculty members and academic advisors as reflections in e-portfolio platforms. In terms of personal gain, the majority admitted to increased selfconfidence to communicate in English as a result of participating in public speaking, presentations and a variety of volunteering projects.Suggestionsforfuture includeout campus activities, useof high technology digitaltraining materials and diversification of assessmentreflective ofthe complete softskills course